Operational definition of precipitated opioid withdrawal - Dunn, Kelly E.; Bird, H. Elizabeth; Bergeria, Cecilia L.; Ware, Orrin D.; Strain, Eric C.; Huhn, Andrew S. (Frontiers in Psychiatry, 2023)
Background: Opioid withdrawal can be expressed as both a spontaneous and precipitated syndrome. Although spontaneous withdrawal is well-characterized, there is no operational definition of precipitated opioid withdrawal. Methods: Persons (N=106) with opioid use disorder maintained on morphine received 0.4mg intramuscular naloxone and completed self-report (Subjective Opiate Withdrawal Scale; SOWS), visual analog scale (VAS) Bad Effects and Sick, and observer ratings (Clinical Opiate Withdrawal Scale; COWS). Time to peak severity and minimal clinically important difference (MCID) in withdrawal severity were calculated. Principal Component Factor Analyses (PCA) during peak severity were conducted and analyzed with repeated measures analyses of variance (ANOVA). Results: Within 60 minutes, 89% of persons reported peak SOWS ratings, and 90% of persons had peak COWS scores as made by raters. Self-reported signs of eyes tearing, yawning, nose running, perspiring and hot flashes and observed changes in pupil diameter and rhinorrhea/lacrimation were uniquely associated with precipitated withdrawal. VAS ratings of Bad Effect and Sick served as statistically significant severity categories (0, 1-40, 41-80, 81-100) for MCID evaluations and revealed participants identified an increase of 10 (SOWS; 15% maximum percent effect [MPE]) and 6 (COWS; 12% MPE) points as meaningful shifts in withdrawal severity indicative of precipitated withdrawal. Conclusion: Data suggested that a change of 10 (15% MPE) and 6 (12% MPE) points on the SOWS and COWS, respectively, that occurred within 60 minutes of antagonist administration was identified by participants as a clinically-meaningfully increase in symptom severity. These data provide a method to begin examining precipitated opioid withdrawal.